Trazos de la novela autoficcional en cuatro autores antioqueños - Rico, Wilber (Folios, revista de la Facultad de Comunicaciones y Filología, 2025)
The so-called Antioquian literary field in contemporary authors is shaped by an attempt of a structuring of the field defined by Bourdieu. This a project emerges under the shelter of the subgenre of autofiction; with post-Garciamarquian authors whose writings of the “self” oppose the older tradicion of local realism or the Caribbean literary field. In the shadow of this autofictional aesthetics, we find self-narrations by Fernando Vallejo, Héctor Abad Faciolince, Albalucía Ángel,and Tomás González, which are considered in this article.